Evaluation of Three Anti-SARS-CoV-2 Serologic Immunoassays for Post-Vaccine Response. (13th September 2021) - Di Meo, Ashley; Miller, Jessica J; Fabros, Anselmo; Brinc, Davor; Hall, Victoria; Pinzon, Natalia; Ierullo, Matthew; Ku, Terrance; Ferreira, Victor H; Kumar, Deepali; Pasic, Maria D; Kulasingam, Vathany
Abstract: Background: In North America, both messenger RNA (mRNA) vaccines, Pfizer-BioNTech BNT162b2, and Moderna mRNA-1273, each utilizing a 2-dose regimen, have started to be administered to individuals. Methods: We evaluated the quantitative serologic antibody response following administration of either a single dose or both doses of an mRNA severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine in a cohort of 98 participants (88 healthcare workers [HCW] and 10 solid organ transplant [SOT] recipients). Antibody levels were compared across 3 immunoassays: Elecsys Anti-SARS-CoV-2 S (Roche Diagnostics), SARS-CoV-2 TrimericS IgG (DiaSorin), and SARS-CoV-2 IgG II Quant (Abbott). Results: Among HCW, sensitivity ranged from 100% (Roche), 99% (Abbott) and 98% (DiaSorin). The SARS-CoV-2 IgG II Quant and SARS-CoV-2 TrimericS IgG assays showed good agreement with a Pearson correlation coefficient of R = 0.95. Pearson correlation coefficients of R = 0.82 and 0.83 were obtained for Elecsys Anti-SARS-CoV-2 S vs SARS-CoV-2 TrimericS IgG and SARS-CoV-2 IgG II Quant vs Elecsys Anti-SARS-CoV-2 S, respectively. Significant differences in antibody levels between HCW and SOT recipients were observed. A decrease in antibody levels from time of vaccine administration to blood draw was evident. Among those with a second dose, an increase in antibody levels with increased time between administration of the first and second dose was observed. Conclusions: The absolute values generated from each of the assay platforms are not interchangeable. Antibody levels differed with increased time between vaccine administration and with increased time between administration of the first and second dose. Further, significant differences in antibody levels between HCW and SOT recipients were observed.